IDENTIFICAÇÃO E CARACTERIZAÇÃO DA MICROBIOTA ASSOCIADA DE DUAS VARIEDADES DE CANA-DE-AÇÚCAR (Saccharum spp.) - GOMEZ, Claudia Estela Barreto; MASCARENHAS, Maria do Socorro; FIGUEIREDO, Dorivan Rios; SANTIAGO, Etenaldo Felipe; BATISTOTE, Margareth (ANAIS DO ENIC, 2025)
-